Cervical cancer screening in immigrant women in Italy: a survey on participation, cytology and histology results. Issue 4 (July 2016) - Campari, Cinzia; Fedato, Chiara; Iossa, Anna; Petrelli, Alessio; Zorzi, Manuel; Anghinoni, Emanuela; Bietta, Carla; Brachini, Angela; Brezzi, Silvia; Cogo, Carla; Giordano, Livia; Giorgi, Daniela; et al.
Abstract : Cervical cancer screening programmes in Italy actively invite all 25–64-year-old resident women for the Pap test every 3 years irrespective of their citizenship. Immigrant women come from countries where screening is absent or poorly implemented and the prevalence of human papillomavirus is often high. These women therefore have significant risk factors for cervical cancer. The Italian Group for Cervical Cancer Screening promoted a survey of all the screening programmes on the participation and the positivity and detection rates in Italian and foreign women in 2009–2011. Aggregated data for participation, cytology results, compliance with colposcopy and histology results were collected, distinguishing between women born in Italy and abroad. All comparisons were age adjusted. Forty-eight programmes out of 120 participated in the immigrant survey, with 3 147 428 invited and 1 427 412 screened Italian women and 516 291 invited and 205 948 screened foreign women. Foreign women had a slightly lower participation rate compared with Italians (39.9 vs. 45.4%), whereas compliance with colposcopy was similar (90%). Foreigners showed a higher risk of pathological findings than Italians: cytology positivity [relative risk (RR)=1.25, 95% confidence interval (CI) 1.24–1.27] and detection rate for cervical intraepithelial neoplasia grade 2 (CIN2) (RR=1.39, 95% CI 1.31–1.47), CIN3 (RR=2.07, 95% CI 1.96–2.18) and cancer (RR=2.68, 95% CI 2.24–3.22). The ratio between cancer and CIN was higher in immigrants (0.06 vs. 0.04, P <0.01). Foreign women had a higher risk of cervical precancer and cancer. Because of their high risk and because opportunistic screening does not cover this often disadvantaged group, achieving high participation in screening programmes for foreigners is critical to further reducing the cervical cancer burden in Italy.